PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE DEMONSTRASI DI SEKOLAH DASAR - Yoverina, Yova -; Zuryanty, Zuryanty; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is motivated by the low learning outcomes of science students in grade V SDN 17 Bunian Payakumbuh. This research is a classroom action research (PTK) which uses qualitative and quantitative approach. The results showed an increase in: (a) Planning in cycle I was 84% (B) increased in cycle II to 93% (SB), (b) Implementation cycle I teacher aspect 77% (C) (C) increase in cycle II to 91% (SB), (c) Student learning outcomes cycle I mean value 84 (B) increase in cycle II to 93 (SB). From the research results can be concluded that the method of demonstration can improve the learning outcomes of science students of grade V SDN17 Bunian Payakumbuh.